The Utilization of Technological Media in Arabic Language Instruction - Muh. Sany Segaf; M. Al Fikri Amrullah Sani; Moh. Haryadi; Larasati Praba Ningsih; Nurul Sefiatul Hikmah; Nehayati; Nurul Fatmiatu; Refa Rahmatul Ulya (Formad English Foundation NTB Jakarta, 2026)
The rapid development of digital technology has transformed Arabic language instruction by introducing various forms of technological media that enhance learning effectiveness, engagement, and accessibility. This study aims to systematically review and synthesize existing literature on the utilization of technological media in Arabic language instruction, focusing on how these technologies are conceptualized, their impacts on learning outcomes and student engagement, and the challenges associated with their implementation. A systematic literature review approach was employed by analyzing peer-reviewed journal articles and academic books published between 2016 and 2025. Data were collected through structured database searches and selected based on relevance, credibility, and topical focus. The data were then analyzed using thematic analysis to identify recurring patterns and themes across the literature. The findings reveal that technological media are widely conceptualized as tools for fostering interactive, student-centered, communicative, and constructivist learning environments. The review also indicates that technological media significantly improve students’ language proficiency, particularly in vocabulary acquisition, grammatical understanding, and integrated language skills, while also enhancing motivation, participation, and learner confidence. However, several challenges persist, including limited teacher digital literacy, inadequate training, infrastructure constraints, and the digital divide, which hinder optimal implementation. In conclusion, technological media play a crucial role in advancing Arabic language instruction by improving learning outcomes and engagement, yet their effectiveness depends on teacher competence, institutional support, and technological readiness. The study highlights the need for comprehensive strategies to optimize technology integration in Arabic language education.